Gut check on diabesity: leveraging gut mechanisms for the treatment of type 2 diabetes and obesity. (December 2017) - Will, Sarah; Hornigold, David C; Baker, David J; Coghlan, Matthew P; Mesquita, Malcolm; Trevaskis, James L; Naylor, Jacqueline
Highlights: GLP-1R agonists approved for both diabetes and obesity. Combination strategies best mimic bariatric surgery effect. Emerging oral formulations. Abstract : Gut hormones have long been understood to regulate food intake and metabolism. Bariatric surgery significantly elevates circulating gut hormone levels and is proven to affect acute remission of type 2 diabetes before any weight loss is observed. Subsequent weight loss is accrued over weeks to months but is sustained into the long term. Hence, there exists great enthusiasm to recapitulate these changes in gut hormones in the form of novel combination drugs for type 2 diabetes and obesity.